2022
DOI: 10.1126/sciadv.abn7006
|View full text |Cite
|
Sign up to set email alerts
|

ECM-mimetic immunomodulatory hydrogel for methicillin-resistant Staphylococcus aureus –infected chronic skin wound healing

Abstract: The treatment of difficult-to-heal wounds remains a substantial clinical challenge due to deteriorative tissue microenvironment including the loss of extracellular matrix (ECM), excessive inflammation, impaired angiogenesis, and bacterial infection. Inspired by the chemical components, fibrous structure, and biological function of natural ECM, antibacterial and tissue environment–responsive glycopeptide hybrid hydrogel was developed for chronic wound healing. The hydrogel can facilitate the cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(98 citation statements)
references
References 59 publications
1
87
0
Order By: Relevance
“…The collagen sponge with anti-infective bioactive molecules also effectively restored the normal function of fibroblasts and keratinocytes in infectious wounds (Ramanathan et al, 2017). The latest research shows that glycopeptide hydrogel accelerates the reconstruction of fullthickness diabetes and scalded skin infected by methicillinresistant Staphylococcus aureus (MRSA) by coordinating a large number of M2-type macrophages, reducing inflammation and promoting angiogenesis (Liu W. et al, 2022). We summarize the evolution of wound dressing function through a set of figures (Figure 2).…”
Section: Sterilization Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen sponge with anti-infective bioactive molecules also effectively restored the normal function of fibroblasts and keratinocytes in infectious wounds (Ramanathan et al, 2017). The latest research shows that glycopeptide hydrogel accelerates the reconstruction of fullthickness diabetes and scalded skin infected by methicillinresistant Staphylococcus aureus (MRSA) by coordinating a large number of M2-type macrophages, reducing inflammation and promoting angiogenesis (Liu W. et al, 2022). We summarize the evolution of wound dressing function through a set of figures (Figure 2).…”
Section: Sterilization Characteristicsmentioning
confidence: 99%
“…In addition, the presence of a large number of proteases in the microenvironment of diabetes Frontiers in Bioengineering and Biotechnology frontiersin.org wounds leads to the degradation of GFS, which further hinders angiogenesis and diabetes wound healing. Some studies have shown that ECM simulation and immune regulation can be achieved through the modification of the material itself (Liu W. et al, 2022), to achieve the antibacterial effect. However, the healing of diabetes wounds does not depend solely on the antibacterial effect.…”
Section: Purpose Of Active Ingredient Accumulationmentioning
confidence: 99%
“…The treatment of infected wounds not only required an upfront antibacterial and anti-infective strategy but also needed the suppression of chronic inflammation during the healing process. Many effective approaches have been proposed for bacterial inhibition and promoting infected wound healing. , For example, metal nanoparticles could defend against bacteria through the release of metal ions, photothermal and photocatalytic ability, immunomodulatory hydrogel , that orchestrated a pro-regenerative response by abundant macrophages, and attenuated inflammation. Ce/Cu-DBs possessed a heterojunction structure composed of two nanozymes.…”
Section: Resultsmentioning
confidence: 99%
“…Many effective approaches have been proposed for bacterial inhibition and promoting infected wound healing. 36,37 For example, metal nanoparticles 38 could defend against bacteria through the release of metal ions, photothermal and photocatalytic ability, immunomodulatory hydrogel 39,40 that orchestrated a pro-regenerative response by abundant macrophages, and attenuated inflammation. Ce/Cu- in the efficiency of ROS production and scavenging in the pH 5−7 range.…”
Section: Ros Regulatory Effect Of Ce/cu-dbs On Infectedmentioning
confidence: 99%
“…Both approaches neglected the consideration of potential septic symptoms, while the latter approach necessitated near-infrared irradiation, which provides a severe drawback compared to the use of our Pt-NP/UiO-66 MOFs, requiring no additional light triggering. Other approaches have advocated a preference for stimulating polarization toward the M2-phenotype to facilitate angiogenesis and blood vessel maturation in order to accelerate healing of the skin after chronic wound infection . Whereas this may be preferable in order to stimulate tissue healing, bacterial source elimination, particularly of pathogens involved in life-threatening sepsis, may be considered a first priority from a clinical perspective.…”
Section: Discussionmentioning
confidence: 99%